Life cycle analysis of hydrothermal carbonization of olive mill waste: Comparison with current management approaches. (20th January 2017) - Benavente, Verónica; Fullana, Andres; Berge, Nicole D.
Abstract: Significant efforts have been direct towards developing environmentally sustainable and economically beneficial treatment of olive mill wastes. Recently, hydrothermal carbonization (HTC) has been shown to be a potentially beneficial approach for the treatment of olive mill wastes. When considering the use of HTC to treat these wastes, however, it is critical that its environmental implications be evaluated and subsequently compared to other commonly used treatment approaches. In this study, the environmental impacts associated with using HTC to treat olive mill wastes were evaluated and compared to aerobic composting, anaerobic digestion, and incineration using life cycle assessment. Results indicate that HTC coupled with subsequent energy recovery from the combustion of the generated hydrochar results in net environmental benefits and that the energy offsets derived from electricity production from hydrochar combustion are critical to achieving these savings. In addition, results indicate that HTC process water discharge significantly influences system environmental impacts, indicating that research investigating treatment alternatives is needed. Changes in carbonization temperature and hydrochar moisture content also influence system environmental impact, suggesting that both are important when considering possible industrial applications. In comparison with current management approaches, alternatives using HTC are more environmental advantageous than composting and anaerobic digestion. However, the use of HTC is not as environmentally advantageous as incineration with energy recovery because 45-35% of the energy contained in the olive mill waste is lost during HTC. However, if the electricity recovery efficiency from incineration increases to greater than 30%, the environmental impacts associated with HTC and subsequent energy generation are equal to or better than direct TPOWM incineration with energy recovery. It is recommended that future research efforts focus on the evaluation of appropriate and environmentally beneficial HTC process water treatment approaches and methods to improve the energetic retention efficiencies of the hydrochar. Highlights: Environmental impacts associated with TPOMW treatment is evaluated using LCA. Thermal treatment of TPOMW is more environmentally advantageous than biological treatment. Energy recovery is critical in reducing system environmental impact. Incineration with energy recovery has a lower impact than HTC, but operational challenges remain. Increase hydrochar energy recovery efficiency and treat liquid emissions to reduce impact.